MENJELAJAH LUKA BATIN PENDEKATAN PSIKOLOGI KONSELING TERHADAP KESENGSARAAN MAERA DALAM NOVEL ‘KRESEK HITAM’ - Rohmatin, Kartika Nur Khozaainah (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2024)
Emotional pain is a psychological condition that is often experienced by people who have experienced trauma or deep emotional difficulties. Maera, the main character in the novel "Kresek Hitam" by Honey Dee, experiences severe emotional wounds due to the injustice and family problems she experiences. The aim of this research is to study psychological counseling methods to heal Maera's inner wounds in the novel "Kresek Hitam". This research uses a qualitative approach and analyzes relevant counseling psychology theories. The research results showed that the injustice and family problems experienced by Maera had an impact on her emotional and psychological condition. Maera received help in improving her mental health and repairing her inner trauma through a counseling psychology approach used through individual counseling methods and group therapy.